Exchange market pressure in identifying currency crisis and its effectiveness in monetary policy in selected Asian countries - Tey, Sheik Kyin (2018)
The occurrence of the currency crisis has increased due to the growth of globalisation and the emergence of the integrated international financial market. Hence, the recent crisis justifies the requirement for the policymakers to comprehend the contagion to avoid and manage the widespread of a future crisis, particularly for Asian countries which aim towards a more comprehensive regional monetary and financial integration with the world. Thus, this study examined the various transmission mechanisms that propagated and amplified the shocks from one country to another country in Asia, motivated by the financial crisis turbulence in Asian countries and the doubts of optimal responses for the crisis. In particular, this study also investigated the transmission of global shock between economies that focus on ‘trade’ and ‘financial’ linkages and the relationship between currency crisis and monetary policy in four countries, namely Indonesia, Korea, Malaysia and the Philippines. In contrary to the literature, this study attempted to analyse the impacts of specific actions or policies on individual countries which can provide insights for each sample country with different macroeconomic fundamentals. In addition, this study also dated the currency crisis with more sophisticated statistical tests and methods, such as Extreme Value Theory (EVT). Apart from that, this study applied the Structural Vector Autoregressive (SVAR) models to analyse the effectiveness of monetary policy in decreasing currency pressure. In fact, the findings of the study provide valuable implications for the policy authorities. Thus, in this study, the main findings are: (1) more flexible currency is associated with higher volatility; (2) the higher degree of trade openness assists to amplify the impact of shocks in the economy; (3) the currency crisis is transmittable among major trade partners and/or competitors; (4) the economic fundamental is related to the incidence of currency crisis and supports the first-generation model of speculative attacks; (5) the responses of the currency pressure to monetary policies shocks are varied between Asian financial crisis and global financial crisis; and (6) the monetary policy stances are ineffective in decreasing currency pressure. Since the results revealed that the crisis is transmitted through trade linkage, policy authorities should be more cautious in pursuing external liberalization and deregulating the market. Thus, to prevent the initiation of a currency crisis, the policy authorities should pursue the policy that lead to macroeconomic stability such as budget balance.